Genital exam, a missed piece of the puzzle in medical diagnosis, can be lifesaving in men: A lesson from a case of a state of shock due to duodenal metastasis of testicular choriocarcinoma - Zeighami, Shahryar (Qatar Med J, 2020)
Here we reported a case of a 17-year-old man with a history of weakness, vertigo, nausea, vomiting and dark stool within the last three months prior to admission. He was taken to the Emergency Room in a state of shock. After resuscitation, vital signs became stable, but due to low hemoglobin (HB = 5 g/dl), to find the source of bleeding, endoscopy was performed and a mass in the duodenum was detected. The pathology report was metastatic germ cell tumor. On genital physical exam (PE) there was a mass in the right testis; thus, the patient underwent radical orchiectomy and choriocarcinoma was diagnosed. The patient then received chemotherapy for six months, and he responded well to the treatment. This case report confirmed that genital PE should be part of a patients visit, even when we cannot find logical relation between clinical presentation and genital PE.